Economics analysis of cassava tillage - Souza, Remy Farias de; Silva, Ivandro de França da; Silveira, Flávio Pereira da Mota; Diniz Neto, Manoel Alexandre; Rocha, Igor Tenório Marinho da (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2014)
World agriculture is constantly affected by unfavorable edaphoclimatic factors, constituting challenges that need to be overcome. However, the cultivation of cassava is widely used in many tropical regions of the world, justified by characteristics of rusticity and adaptation of culture, which is very important to its cultivation by farmers. The objective of this research was to conduct an analysis of economic viability in the cultivation with cassava. Was carried out a survey of productivity and economic viability of five studies using the following economic indicators: gross revenue, gross income, relationship benefit/costand breakeven point, at the experimental station of Empresa Estadual de Pesquisa Agropecuária da Paraíba (EMEPA -PB), in Alagoinha, Paraíba. It was observed that the system of cultivation with cassava showed economic viability in all surveys.